Characterization of multicomponent herbal preparations by the integral indicators — antioxidant activity and total content of polyphenols - Lipkovska, N. O.; Barvinchenko, V.M.; Turov, V.V.; Kartel, M.T. (Reports of the National Academy of Sciences of Ukraine, 2014)
The antioxidant and spectral properties of aqueous extracts of dietary supplements of the Fitosyl series are investigated. It is established that the antioxidant activity of herbal remedies is caused by the presence of natural polyphenols — flavonoids and hydroxycinnamic acids. A new methodological approach to the wavelength selection at the spectrophotometric analysis of multicomponent herbal preparations is proved. It is shown that the methods presented are suitable for the quality control of herbal remedies and foods of the plant origin by such integral parameters as the antioxidant activity and the total polyphenol content.